Recurrent Wheezing in Pre-school Age: Not Only Airway Reactivity! - Roversi, Marco; Porcaro, Federica; Francalanci, Paola; Carotti, Adriano; Cutrera, Renato (Frontiers in Pediatrics, 2020)
Background. About a fifth of all mediastinal masses are primary cysts arising in the absence of other underlying pathology. Bronchogenic cysts are the most frequent type, but are rarely responsible for upper airways compression as they often develop in the peripheral branches of the tracheobronchial tree and are often asymptomatic. Case presentation. We report the case of a 6-months-old child admitted for acute respiratory distress and wheezing. The nocturnal polygraphy showed an underlying obstructive disorder that was investigated via digestive and airway endoscopy. The latter proved a marked reduction of the tracheal lumen and the chest CT scan confirmed the presence of a wide mediastinal cyst compressing the trachea. The mass, later identified as a bronchogenic cyst, was surgically removed with complete resolution of the patient’s respiratory symptoms. Discussion. Our case shows that differential diagnosis of wheezing in children should encompass causes others than asthma, thus prompting further evaluation and management.